2007
DOI: 10.1088/0967-3334/28/10/n01
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory characteristics of acupuncture points obtained by laser Doppler flowmetry

Abstract: Acupuncture points (acupoints) form part of the meridian system that constitutes the most fundamental concept in oriental medicine, but their physiological basis has not been clarified. In this study we employed laser Doppler flowmetry (LDF) to extract the microcirculatory characteristics of acupoints and their surrounding tissues, and we interpreted the results from the viewpoint of microcirculatory physiology. Three groups of measurements were performed focusing on the following two important acupoints in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 16 publications
2
36
0
Order By: Relevance
“…15 According to the previous study, the MBF was larger at the acupoints than in their surrounding tissues, which indicates that the MBF can be used as an index for discriminating differences in the microcirculatory conditions between acupoints and their surrounding tissues. 16 Thus in this study, the cross-interaction of Hegu acupoints through the index of the change ratio of MBF was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…15 According to the previous study, the MBF was larger at the acupoints than in their surrounding tissues, which indicates that the MBF can be used as an index for discriminating differences in the microcirculatory conditions between acupoints and their surrounding tissues. 16 Thus in this study, the cross-interaction of Hegu acupoints through the index of the change ratio of MBF was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…CBF and tissue oxygenation measurements play an important role in evaluating various conditions such as vasospasm, ischemia, injury and recovery processes and cutaneous implant function [1,2]. The ability to monitor non-invasively changes in the skin microcirculation level leads to improvements both in diagnosis and treatment of patients [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the mean of laser Doppler flowmetry (LDF) signals were significantly larger at the acupoints than in their surrounding tissues, which indicated a large volume of blood delivery to the microvascular beds of acupoints. These results indicate that the physical properties of the vascular structure of acupoints may affect the perfusion resistance, and modulate the microcirculatory perfusion [32].…”
Section: Evaluation Of the Proposed Blood Flow Modulation Modelmentioning
confidence: 77%